Affinity-based engineering of carbon nanotube embedded polyamide membranes for simultaneous desalination and boron removal - Kurklu-Kocaoglu, S.; Guvensoy-Morkoyun, A.; Yildirim, C.; Velioglu, S.; Ahunbay, M. G.; Tantekin-Ersolmaz, S. B. (Elsevier, 2024)
Reverse osmosis (RO) is the leading technology for obtaining drinking and irrigation water from seawater. Although currently developed RO membranes achieve high salt rejection; several challenges exist, such as permselectivity trade-off, biological/chemical contamination, and insufficient retention of small and neutral molecules like boric acid. Due to its toxicity to living organisms and strictly monitored levels in potable water, removal of boron has gained considerable attention in RO industry. Thin film nanocomposite (TFN) membranes have emerged by incorporating nanomaterials with superior water/salt selectivity into polyamide (PA) layer of composite membranes. For the first time, our group investigated the potential of carboxylated carbon nanotube (CNT) embedding in the selective layer of TFN membranes for boron removal. Within this frame, we hypothesize that embedding fillers with low boron affinity accompanied by high water permeability in the selective layer of TFN membranes improves boron removal without suffering from the permselectivity trade-off. In this study, we investigated the boron removal performance of functionalized CNT (f-CNT) embedded TFN membranes. Initially, CNTs were functionalized with three different functional groups (namely, biotin (BIO), 8-amino caprylic acid (ACA), and zwitterion (ZWT)) to narrow down the tube entrance, provide repulsive electrostatic interactions with boron, and interfere with the hydrogen bonding between water and boric acid molecules. Then, TFN membranes incorporating f-CNTs were fabricated, characterized, and tested. Showing high compatibility with PA, ZWT functionalization has increased water/boron selectivity of TFN membranes by 66% and water permeability by 44%, while maintaining the salt rejection at 98%. Furthermore, we employed molecular dynamics simulations and potential of mean force calculations to elucidate the boron exclusion mechanism in fCNTs. With its flexible structure and gate-keeper ability, ZWT functional group was found to show the highest energy barrier against boron transport. Hence, engineering CNT/PA TFN membranes to promote steric hindrance and decrease solute affinity is promising for efficient removal of detrimental small molecules from seawater.
Keywords: Thin film nanocomposite membrane; Reverse osmosis; Boron removal; CNT; Functionalization